3D FEM investigation on bending failure mechanism of column inclusion under embankment load - S. Shrestha; J.-C. Chai; D. T. Bergado; T. Hino; Y. Kamo (International Association of Lowland Technology, 2015)
Bending failure mechanism of column inclusions in soft clay deposit under embankment loading has been investigated by three dimensional (3D) finite element analyses. Firstly the effectiveness of the numerical procedure has been verified by comparing the simulated and the measured results of a centrifuge model test reported in the literature in terms of lateral displacement, settlement, and the bending moment in the column. Then the effects of the size of the column improved area from the toe toward the center of the embankment, stiffness of the column, the length of the column on the maximum bending moment in the column have been investigated numerically. The numerical results indicate that increase the size of the improved area, reduced the bending moment in the upper part (near ground surface) of the column; increase the stiffness of the column increased the maximum bending moment; and the maximum bending moment occurred at the end of the column in the case of an end bearing column, and in the upper part of the column for a floating column. The numerical results also indicate that when the whole area under the embankment is improved by end bearing columns with an area improvement ratio of 28 % and tensile strength of the column of 100 kN/m2, the embankment load can be applied with a factor of safety of about 2 for bending failure of the columns is about 13 times of the initial undrained shear strength of the soft deposit.